Sea Transport Services in Italy - Papa, Enrica (TeMA - Journal of Land Use, Mobility and Environment, 2009)
Sea transport for passengers is an interesting intermodal transport concept by definition, nevertheless, the concept has not been widely developed in Italy. Normative and infrastructural conditions generally form a major impediment. However in some regions new short sea shipping services , as alternative to public transport services, are being developed. These services have two main objectives: to offer a valid alternative to road public transport in order to reduce transport emission, and to facilitate the coast use for tourist. The paper analyses five study cases where sea public transport have been implemented and are going to be developed. The Campania Region Metrò del Mare represent a model for the rest of Italian regions, as it is the first sea transport system operating from 2001, with nine lines and 23 touristic ports-stations. It is designed as a real sea-metro system with over 270.000 passengers in the seven months when it is active. Another interesting case study is the Genova sea public transport (in Liguria Region), that is operating from 2007. In this area touristic services are working since 1980, but only few years ago a new transport services (Navebus) was developed with the aim of give to commuters a valid alternative to the road private and public transport. The case of the Reggio Calabria-Messina sea metro system, the Lazio Region and MTB Metromarina study cases show good design and opportunities for connecting with a real public transport system major touristic port along the coast. For different reasons these services are not yet implemented. The conclusion of this work shows some point of interest fro sea transport system planning: - To give to sea transport services the assessment of real public transport, in order to receive finances from the region (as in the Campania and Liguria study cases) - To create e integrated fares system in order to facilitate rail, road and sea services for commuters and tourists along the coast (as in Campania Region). - To promote the tourist use of sea services creating a network with the mayor touristic attraction along the coast that will be accessible by the new sea services; - To organize and design the sea services as a metro transport service, with high frequencies and many stops - To renew the tourist ports that will be accessible by the sea services with a “transit oriented approach”. The new interest shown for short sea passenger transport represents an interesting challenge for local administration for give a contribute to the efforts of reducing transport environmental impacts and to promote coastal areas for touristic uses. The Campania region successes in obtain good results, that can be reach also in other Italian and Mediterranean coastal areas.